Strategic Decision Analysis To Manage Competitive Advantage For Shopee Indonesia - Kelvin Kelvin; Santi Novani (Jurnal Studi Manajemen dan Bisnis, 2023)
Shopee Indonesia, a key participant in the dynamic e-commerce landscape, has leveraged the power of innovative digital solutions to reach and serve a diverse customer base. Despite its success, Shopee faces unique challenges and opportunities that influence its strategic decisions and market position, just like any other competitive industry player. Shopee benefits from the rapid development of Indonesia's internet and e-commerce penetration rate as well as increase in Micro, Small, and Medium-Sized Enterprises (MSME) participation across the nation. However, Shopee confronts intense competition from emerging platforms such as Tiktok Shop, particularly in the Fashion and Beauty category. Shopee's extensive coverage of Stock Keeping Units (SKUs) and comprehensive selection of products are distinguishing features that provide customers with a vast array of options. Additionally, Shopee's marketing strategies and free shipping promotions distinguish it in the market. Notably, Shopee's extensive payment options, such as Cash-on-Delivery, increase its accessibility for a vast array of consumers. However, User Interface and User Experience (UI/UX), loyalty and rewards programs, customer service quality, personalized purchasing experience, and engaging features such as Shopee Games, Shopee Live, and Shopee Video are identified as key areas for improvement. Strategic investments in enhancing UI/UX, providing engaging loyalty programs, delivering exceptional customer service, and leveraging innovative technology to curate personalized purchasing experiences can elevate Shopee's position in the e-commerce industry. Shopee is poised to capitalize on its strengths, resolve its weaknesses, and take advantage of available opportunities to maintain its leadership position in the Indonesian e-commerce market, which is constantly evolving.